A test of the interpersonal theory of suicide in a large sample of current firefighters. (30th June 2016) - Chu, Carol; Buchman-Schmitt, Jennifer M.; Hom, Melanie A.; Stanley, Ian H.; Joiner, Thomas E.
Abstract: Recent research suggests that firefighters experience elevated rates of suicidal ideation and behaviors. The interpersonal theory of suicide may shed light on this finding. This theory postulates that suicidal desire is strongest among individuals experiencing perceived burdensomeness and thwarted belongingness, and that the combination of suicide desire and acquired capability for suicide is necessary for the development of suicidal behaviors. We tested the propositions of the interpersonal theory in a large sample of current United States firefighters ( N =863). Participants completed self-report measures of perceived burdensomeness, thwarted belongingness, fearlessness about death (FAD; a component of acquired capability), and career suicidal ideation and suicide attempt history. Regression models were used to examine the association between interpersonal theory constructs, career suicidal ideation severity, and the presence of career suicide attempts. In line with theory predictions, the three-way interaction between perceived burdensomeness, thwarted belongingness, and FAD was significantly associated with career suicide attempts, beyond participant sex. However, findings were no longer significant after accounting for years of firefighter service or age. Contrary to predictions, the two-way interaction between perceived burdensomeness and thwarted belongingness was not significantly related to career suicidal ideation severity. Applications of the theory to firefighters and future research are discussed. Highlights: We test the interpersonal theory of suicide (ITS) in a sample of firefighters. We correlate ITS variables with career suicidal ideation and attempts. Perceived burdensomeness (PB)×thwarted belongingness (TB) did not relate to ideation. In line with the theory, PB×TB×acquired capability related to presence of attempts.